Why students fail, and how they can succeed – a case study focusing on repeating students in a module on technology management - Arthur James Swart (JIPTEK: Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2025)
Students in higher education are allowed to exceed the alotted time of a given qualification by a set value as stipulated by an institution. This accounts for repetition where a student may fail a module and then re-register for it. The purpose of this article is to explore why electrical engineering students failed a compulsory second-year module in a BEngTech qualification, and what contributed to their academic success during their second (or even fourth) attempt. An exploratory case study is used focusing on a single module, called Technology Management III, offered at the Central University of Technology, Free State in South Africa. The results indicate that in 2024, one student was repeating the module for the fourth time, while 21 students were attempting it for a second time. A semi-structurd interview was used were three specific questions were asked. Firstly, many of the students indicated that they had originally failed the module because they did not attend class or had faced personal challenges or did not understand how to answer the theory-based questions. Secondly, many students then noted that their current success could be attributed to dedicating more time to the module, attending class and joining a study group. Finally, many students provided the following advice to future students: Attend, participate and take notes in class and then dedicate time to the module through self-reflection. It is recommended to share the results of this study with future students as part of vital academic student support.